Formulation of an environment and social impact assessment tool for small scale economic activities in coastal areas in the Philippines - Cabrido, Candido A., Jr. (2015)
This study formulated an Environment and Social Impact Assessment (ESIA) tool that is applicable to small scale economic activities (SSEAs) or livelihood projects commonl;y undertaken in coastal areas by fishing communities. The cumulative adverse environmental impacts of the growing number of SSEAs such as marine culture fisheries and agro processing are now becoming alarming because these types of small scale individual projects or economic and livelihood activities are not regulated under the Environmental Impact Statement (EIS) system of the Environmental Management Bureau (EMB). The EIS system covers medium to large scale development projects (ECPs) or those projects located in environmentally critical areas (ECAs) identified by EMB. SSEAs also fall below the project size thresholds set under the latest regulations of the EMB. Hence, a regulatory and planning tool needs to be developed and operationalized at the Local Government Unit (LGU) level to enable the conservation of coastal habitats and resources while sustaining the stream of benefits from the SEEAs. the ESIA is not a tool designed to address the need for capacitating LGUs to sustain the ecological integrity and prodyuctivity of their coastal habitats and resources. The formulation and institutionalization process of the ESIA tool consisted of six key steps: (1) review of pertinent laws and regulations and related studies; (2) profiling of coastal-based SEEAs; (3) designing of tool structure, content and uses; (4) crafting of ESIA monitoring framework; (5) establishing the framework for ESIA application in local development planning and (6) establishing the scheme for ESIA institutionalization in the LGU governance system. Details of the formulation process are discussed in this policy research study.
Keywords: Environmental impact analysis; Coastal zone management